JURIDICAL ANALYSIS OF SUPERVISION OF PRISONERS FOR ALL FORMS OF VIOLATION OF THE LAW TO REALIZE PUBLIC ORDER (Research Study at Class IIA Batam State Detention Center) - Ray Leonard Hutabarat, Parley; Washliati, Laily; Nofrial, Ramon (RADJA PUBLIKA, 2023)
In the context of the state, it is regulated in a criminal justice system as a unitary institution that handles legal issues in the country. The Correctional System is an arrangement regarding the direction and limits as well as ways of fostering prisoners based on Pancasila which is carried out in an integrated manner between coaches, fostered, and the community to improve the quality of prisoners so that they are aware of mistakes, improve themselves, and not repeat criminal acts so that they can be accepted again by the community. , can play an active role in development, and can live normally as good and responsible citizens. Correctional Institutions in dealing with every perpetrator of law violations must prioritize the principles of treatment that aim to